2017
DOI: 10.18203/2320-1770.ijrcog20171399
|View full text |Cite
|
Sign up to set email alerts
|

A study of vaginal misoprostol tablet versus intra cervical dinoprostone gel for the induction of labour

Abstract: Background: This was a comparative study conducted to compare the effectiveness of 25 microgram of intravaginal misoprostol with intracervical dinoprostone gel in terms of efficacy of drug, feto-maternal outcome, side effects and complications of drugs.Methods: 400 nulliparas at term, admitted for induction of labor were included in this study. They were randomly selected to receive either intravaginal misoprostol or intracervical dinoprostone gel. Group A (200 women) recieved tablet misoprostol 25 micrograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
1
0
0
Order By: Relevance
“…APGAR score was better in Group I compared to Group II similar to studies done by Soilemetzidis M et al 10 Need for NICU admission was similar in both the groups similar to study by Badlani CN et al 11 Study done by Papanikolaou EG showed more neonates were admitted to the intensive neonatal unit in the misoprostol group compared to the dinoprostone group.…”
Section: Discussionsupporting
confidence: 79%
“…APGAR score was better in Group I compared to Group II similar to studies done by Soilemetzidis M et al 10 Need for NICU admission was similar in both the groups similar to study by Badlani CN et al 11 Study done by Papanikolaou EG showed more neonates were admitted to the intensive neonatal unit in the misoprostol group compared to the dinoprostone group.…”
Section: Discussionsupporting
confidence: 79%